2006
DOI: 10.1128/mcb.00816-06
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Yin-Yang Regulators and a Phosphorylation Consensus for Male Germ Cell-Associated Kinase (MAK)-Related Kinase

Abstract: MAK (male germ cell-associated protein kinase) and MRK/ICK (MAK-related kinase/intestinal cell kinase) are human homologs of Ime2p in Saccharomyces cerevisiae and of Mde3 and Pit1 in Schizosaccharomyces pombe and are similar to human cyclin-dependent kinase 2 (CDK2) and extracellular signal-regulated kinase 2 (ERK2). MAK and MRK require dual phosphorylation in a TDY motif catalyzed by an unidentified human threonine kinase and tyrosine autophosphorylation. Herein, we establish that human CDK-related kinase CCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
130
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 78 publications
(139 citation statements)
references
References 70 publications
9
130
0
Order By: Relevance
“…9. Briefly, cells were harvested in ice-cold PBS and lysed in lysis buffer (50 mM Tris-HCl (pH 7.4), 150 mM NaCl, 1% Nonidet P-40, 2 mM EGTA, and supplemented with complete protease inhibitors (Roche), 1 mM Na 3 VO 4 , 1 M microcystin LR, and 5 mM ␤-glycerophosphate).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…9. Briefly, cells were harvested in ice-cold PBS and lysed in lysis buffer (50 mM Tris-HCl (pH 7.4), 150 mM NaCl, 1% Nonidet P-40, 2 mM EGTA, and supplemented with complete protease inhibitors (Roche), 1 mM Na 3 VO 4 , 1 M microcystin LR, and 5 mM ␤-glycerophosphate).…”
Section: Methodsmentioning
confidence: 99%
“…Unlike MAPKs, the ICK kinase activity cannot be acutely stimulated by serum or growth factors. Our prior studies suggest that protein phosphatase 5 (7) and CCRK/CDK20 (cell cycle-related kinase/cyclin-dependent kinase 20) (8) are putative upstream yin-yang regulators for the phosphorylation of ICK Thr-157 (9). We have shown that oxidative stress, which activates protein phosphatase 5, is able to inactivate ICK by dephosphorylating Thr-157 within the TDY motif (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, PP5 has been shown to associate with several proteins that affect signal transduction networks [1][2][3][4][5][6][14][15][16][17][18]. When PP5 is displaced from these biological partners, phosphatase activity is greatly decreased.…”
Section: Expression and Purification Of Pp5cmentioning
confidence: 99%
“…However, the advent of siRNA and antisense oligonucleotides capable of specifically suppressing individual phosphatases has greatly aided our understanding of the biological roles of ser/thr protein phosphatases. From such studies serine/threonine protein phosphatase type 5 (PP5) has emerged as an important regulator of hormone/stress-induced signaling networks that propagate cellular responses controlling growth and stress-induced apoptosis [1][2][3][4][5][6][7]. Nonetheless, the development of small molecule inhibitors of PP5 has been hampered because human PP5 expressed in bacteria has very low catalytic activity, and the [ 32 P]based phosphatase assays [8][9][10] commonly used to measure activity are not easily adaptable to high throughput screening assays.…”
Section: Introductionmentioning
confidence: 99%